Observational longitudinal cohort study to determine progression to heart failure in a screened community population: the Echocardiographic Heart of England Screening Extension (ECHOES-X) study - Taylor, C; Roalfe, A; Tait, L; Davis, R; Iles, R; Derit, M; Hobbs, F (BMJ Publishing Group, 2014)
OBJECTIVES: Rescreen a large community cohort to examine the progression to heart failure over time and the role of natriuretic peptide testing in screening. DESIGN: Observational longitudinal cohort study. SETTING: 16 socioeconomically diverse practices in central England. PARTICIPANTS: Participants from the original Echocardiographic Heart of England Screening (ECHOES) study were invited to attend for rescreening. OUTCOME MEASURES: Prevalence of heart failure at rescreening overall and for each original ECHOES subgroup. Test performance of N Terminal pro-B-type Natriuretic Peptide (NT-proBNP) levels at different thresholds for screening. RESULTS: 1618 of 3408 participants underwent screening which represented 47% of survivors and 26% of the original ECHOES cohort. A total of 176 (11%, 95% CI 9.4% to 12.5%) participants were classified as having heart failure at rescreening; 103 had heart failure with reduced ejection fraction (HFREF) and 73 had heart failure with preserved ejection fraction (HFPEF). Sixty-eight out of 1232 (5.5%, 95% CI 4.3% to 6.9%) participants who were recruited from the general population over the age of 45 and did not have heart failure in the original study, had heart failure on rescreening. An NT-proBNP cut-off of 400 pg/mL had sensitivity for a diagnosis of heart failure of 79.5% (95% CI 72.4% to 85.5%) and specificity of 87% (95% CI 85.1% to 88.8%). CONCLUSIONS: Rescreening identified new cases of HFREF and HFPEF. Progression to heart failure poses a significant threat over time. The natriuretic peptide cut-off level for ruling out heart failure must be low enough to ensure cases are not missed at screening.